Pemberian Wasiat Wajibah Bagi Non Muslim: Sebagai Rekonstruksi Hukum Keluarga Islam Di Indonesia - Mohammad Yasir Fauzi; Eko Hidayat (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
Normatively, there is no provision in granting a mandatory will for non-Muslims. This legal vacuum encourages the Supreme Court to grant inheritance to non-Muslims through a mandatory will. 3 (three) Supreme Court cassation decisions grant mandatory wills to non-Muslim heirs. This decision is inconsistent with Islamic law and positive law in Indonesia. The provisions of mandatory wills in KHI article 209 are only intended for adopted children and adoptive parents. Islamic law prohibits non-Muslim heirs from inheriting property from a Muslim testator. This study aims to reconstruct the mandatory will law in Indonesia. This study is a field and library research, using a qualitative approach. Data were collected through interviews with 3 (three) Supreme Court Judges who tried and decided the case. The data were supported by 3 (three) Supreme Court Decisions, namely No. 368 K/AG/1995, No. 51 K/AG/1999, No. 16K/AG/2010, and Compilation of Islamic Law (KHI), Civil Code (KUHPdt). Data analysis using Miles and Hubermen analysis. The results of the study indicate that there are no legal provisions for heirs for non-Muslims through mandatory wills in the KHI, KUHPdt or Islamic law. 3 (Three) Supreme Court Decisions that allow heirs for non-Muslims through mandatory wills are decisions that are responsive to social conditions, equality and justice in society. Therefore, it is necessary to reconstruct Article 209 Paragraph (3) of the KHI to be illegitimate children, stepchildren and children of different religions with the testator who do not receive a will are given a mandatory will of up to 1/3 of the testator's inheritance. This reconstruction can be a consideration for the government in renewing inheritance law in Indonesia